2016
DOI: 10.1002/2015sw001355
|View full text |Cite
|
Sign up to set email alerts
|

One year in the Earth's magnetosphere: A global MHD simulation and spacecraft measurements

Abstract: The response of the Earth's magnetosphere to changing solar wind conditions is studied with a 3-D Magnetohydrodynamic (MHD) model. One full year (155 Cluster orbits) of the Earth's magnetosphere is simulated using Grand Unified Magnetosphere Ionosphere Coupling simulation (GUMICS-4) magnetohydrodynamic code. Real solar wind measurements are given to the code as input to create the longest lasting global magnetohydrodynamics simulation to date. The applicability of the results of the simulation depends critical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Recently, many studies have employed global MHD models to study the effect of the IMF in the cross‐section of the magnetotail at lunar distance. Their results confirmed that the twisting of magnetopause results from nonzero IMF B Y (e.g., Facskó et al, ; Gordeev et al, ; Sibeck & Lin, ; Vörös et al, ; Wang et al, ). They also demonstrated that the magnetopause could elongate further along the direction of IMF in the distant magnetotail than in the near‐Earth regions.…”
Section: Introductionsupporting
confidence: 66%
“…Recently, many studies have employed global MHD models to study the effect of the IMF in the cross‐section of the magnetotail at lunar distance. Their results confirmed that the twisting of magnetopause results from nonzero IMF B Y (e.g., Facskó et al, ; Gordeev et al, ; Sibeck & Lin, ; Vörös et al, ; Wang et al, ). They also demonstrated that the magnetopause could elongate further along the direction of IMF in the distant magnetotail than in the near‐Earth regions.…”
Section: Introductionsupporting
confidence: 66%
“…One of the reasons for that is a rare use of global simulations for mapping to the ionosphere, the other-existing problems in the near-Earth region. This type of comparison was reported in a work by Facskó et al (2016), where the authors compared the ionospheric foot points from Grand Unified Magnetosphere Ionosphere Coupling Simulation version 4 and from the T96 empirical model. The determined footprints were in overall agreement (foot point difference in a range 200-600 km) with the T96 in the Northern Hemisphere during quiet conditions and small IMF B y component.…”
Section: Discussionmentioning
confidence: 90%
“…The utility of these simulations is therefore multi-faceted. Firstly, they enable exploration of the basic physics that controls magnetospheric dynamics; here we mention a few illustrative examples: the analysis of Palmroth et al (2006) using the GUMICS code elucidated the fact that mass transport across the magnetopause may be enhanced for northward IMF; investigating the magnetospheric drivers and energy input under different IMF conditions (Raeder et al 2001;Palmroth et al 2003;Pulkkinen et al 2007;Sergeev et al 2008;Yu and Ridley 2009); exploring the temperature asymmetry in the magnetosheath under different solar wind conditions (Dimmock et al 2015); modelling the effects of shocks on the magnetosphere (Andréeová et al 2008;Oliveira and Raeder 2014); and performing large scale statistical studies (Juusola et al 2014;Facskó et al 2016).…”
Section: Global Modelingmentioning
confidence: 99%